A multilayer core-shell structure adsorbent and preparation method thereof

By adjusting the binder content according to different growth stages during the molding process of the multi-layer core-shell structure adsorbent, the problems of spherical and strength of the adsorbent are solved, and the adsorption performance is significantly improved, especially in terms of nitrogen adsorption amount.

CN116474746BActive Publication Date: 2025-04-01CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210045612.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-15
Publication Date
2025-04-01
Estimated Expiration
2042-01-15

AI Technical Summary

Technical Problem

The existing multilayer core-shell structure adsorbents have poor spherical shape and reduced strength during the molding process, and excessive addition of binder will affect the adsorption performance.

Method used

By adding different binder contents of raw powder at different growth stages during the molding process, the content of binder is gradually adjusted, so as to improve the content of effective adsorption components while ensuring the strength and wear performance of the adsorbent.

Benefits of technology

The high strength, good wear performance and significantly improved adsorption performance of the multi-layer core-shell structure adsorbent are achieved, especially in terms of adsorption of nitrogen, which exceeds the traditional method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 109783DEST_PATH_IMAGE001
    Figure 109783DEST_PATH_IMAGE001
Patent Text Reader

Abstract

The present invention discloses a multilayer core-shell structure adsorbent and a preparation method thereof. In the present invention, raw powder mixtures with different binder contents are added at different growth stages of the adsorbent particle size during the molding process; raw powder with less binder is added when the inner core of the adsorbent is molded, and raw powder with more binder is added when the outer layer of the adsorbent grows, thereby obtaining a spherical particle molded body; the obtained spherical particle molded body is post-processed, and dried and calcined to obtain an adsorbent product. While ensuring the strength and abrasion resistance of the molded adsorbent, the method of the present invention increases the content of effective adsorption components in the adsorbent, thereby significantly improving the adsorption performance of the adsorbent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorption separation, and specifically relates to a multi-layer core-shell structure adsorbent and a preparation method thereof. Background Art

[0002] Pressure swing adsorption technology is widely used in the field of gas separation and purification. It has the characteristics of low energy consumption, simple operation and high product purity. The core of pressure swing adsorption technology is the development of high-efficiency adsorbents. In actual use, the adsorbent needs to be prepared into spherical or strip adsorbents with certain strength and wear resistance through a certain method. Currently, spherical adsorbents are more commonly used. A certain amount of binder needs to be added to the adsorbent during the molding process, which is not only beneficial to the molding effect, but also the strength and wear resistance of the molded adsorbent can be enhanced through the calcination treatment of the binder. The greater the amount of binder added, the better the strength and wear resistance of the prepared spherical adsorbent, but it will also reduce the content of effective adsorption materials in the adsorbent, affecting the adsorption performance of the adsorbent.

[0003] Chinese patent CN01113203.5 discloses a method for synthesizing a wear-resistant spherical NaY molecular sieve, wherein one or two of natural kaolin and clinoptilolite are used as raw materials, a small amount of pore expander and reinforcing agent are added, and spherical particles of a certain particle size are preformed by spray granulation, and the granular mineral is roasted and converted into a NaY type molecular sieve under the hydrothermal crystallization conditions of the NaY molecular sieve. However, the spherical adsorbent prepared by the preparation method of the multi-layer core-shell structure material has poor sphericity, and the strength of the adsorbent after the multi-layer core-shell structure and conversion will be reduced.

[0004] Chinese patent CN201710999862.3 discloses a binder-free spherical 5A molecular sieve adsorbent, which mixes NaA molecular sieve and clay, adds an auxiliary agent and mixes evenly, and then puts into a rolling ball device to obtain a small ball, soaks and roasts it with silica sol, and puts it into an aqueous solution of sodium aluminate and sodium hydroxide for hydrothermal crystallization, so that the SiO2 in the precursor and the macroporous pores inside the small ball is converted into NaA molecular sieve, and the crystallized small ball is ion exchanged, dried, and roasted to obtain a binder-free spherical 5A molecular sieve adsorbent. Although the product obtained by this method has a high adsorption capacity, its crystallization process will affect the mechanical properties of the material, and the preparation process is complicated. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies of the prior art, the present invention provides a multi-layer core-shell structure adsorbent and a preparation method thereof.

[0006] According to a first aspect of the present invention, the present invention provides a method for preparing a multi-layer core-shell structure adsorbent.

[0007] A method for preparing a multilayer core-shell structure adsorbent comprises the following steps:

[0008] (1) preparing N kinds of mixtures composed of adsorbent raw powder and binder with different binder contents, respectively, in the order of binder content from low to high, namely mixture 1, mixture 2, ..., mixture N-1 and mixture N, wherein the binder content of two adjacent mixtures differs by 5-50 percentage points;

[0009] (2) Adding a powder mixture to a ball rolling machine for water sprinkling molding, and adding raw materials with different binder contents at different stages of molding; specifically, the method comprises: first, adding mixture 1 to the ball rolling machine for water sprinkling molding; when the diameter of the spherical particles reaches d1, replacing the powder with mixture 2, and continuing water sprinkling molding; when the diameter of the spherical particles reaches d2, replacing the powder with mixture 3, ..., when the diameter of the spherical particles reaches dN-1, switching the powder to mixture N, and continuing water sprinkling molding until the diameter of the spherical particles reaches the designed particle size d, and the ball rolling is terminated;

[0010] (3) The spherical particle molded body obtained in step (2) is post-treated, dried, and calcined to obtain the target adsorbent.

[0011] Furthermore, N is a natural number, and can be any value between 2 and 5, and preferably N is 2 or 3.

[0012] Furthermore, in the N kinds of mixtures, the mass content of the binder is 5%-70%, preferably 7%-60%.

[0013] Furthermore, in step (2), d1 is generally 0.05-0.7 times the designed particle size d, and the difference between the diameters of two adjacent particles is 0.1-0.5 d. When N is 2, d1 is generally 0.05-0.7 d, the content of binder in mixture 1 is 5%-30%, and the content of binder in mixture 2 is 15%-70%. When N is 3, d1 is generally 0.05-0.7 d, d2 is generally 0.5-0.9 d, the content of binder in mixture 1 is 5%-20%, the content of binder in mixture 2 is 10%-60%, and the content of binder in mixture 3 is 15%-70%.

[0014] Furthermore, the adsorbent raw powder in step (1) is selected from one or more of A-type molecular sieve, X-type molecular sieve, Y-type molecular sieve, ZSM-5-type molecular sieve, SAPO-type molecular sieve, etc. The selected adsorbent types include but are not limited to the above types.

[0015] Furthermore, in step (1), the binder is selected from one or more of kaolin, attapulgite, bentonite, etc. The selected binder types include but are not limited to the above types.

[0016] Furthermore, in step (2), the designed particle size d is in the range of 0.1 to 10 mm, preferably 0.5 to 5 mm;

[0017] Furthermore, in step (3), the post-treatment may generally include steps such as roasting, alkali treatment, and calcium ion exchange.

[0018] Furthermore, in step (3), the calcination temperature is 300-850° C., preferably 350-800° C.; and the calcination time is 1-10 h, preferably 2-8 h.

[0019] Furthermore, the alkaline substance described in step (3) is selected from at least one of NaOH, KOH, Ca(OH)2, Na2CO3, NaHCO3, K2CO3, KHCO3, etc., and the mass content of the alkaline substance in the aqueous solution in step (3) is 5% to 60%, preferably 10% to 55%.

[0020] Furthermore, after adding the alkaline substance in step (3), the aqueous solution is heated to 45-100° C., preferably 50-97° C.; the insulation time is 20-400 min, preferably 30-300 min.

[0021] Furthermore, the drying and calcining in step (3) are conventional operations in the art. For example, the drying temperature is generally 45-150°C, preferably 50-140°C; the drying time is generally 0.1-15h, preferably 0.5-12h; the calcining temperature is generally 250-700°C, preferably 300-650°C; the calcining time is generally 0.5-10h, preferably 1-8h.

[0022] According to the second aspect of the present invention, the present invention also provides a multi-layer core-shell structure adsorbent, which is prepared by the method described above.

[0023] Furthermore, the adsorbent of the present invention has a higher molecular sieve content while meeting the use requirements, and its nitrogen adsorption capacity is higher than that of the adsorbent obtained by the traditional method.

[0024] Compared with the prior art, the method of the present invention has the following beneficial effects:

[0025] This solution adds raw powders with different binder contents at different growth stages of the adsorbent particle size during the molding process. Raw powders with less binder are added when the inner core of the adsorbent is molded, and raw powders with more binder are added when the outer layer of the adsorbent grows. While ensuring the strength and abrasion resistance of the final molded adsorbent, this greatly increases the content of effective adsorption components in the adsorbent and significantly improves the adsorption performance of the adsorbent. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with embodiments, but the present invention is not limited to the following embodiments. Without departing from the content and scope of the present invention, changes in implementation should be included in the technical scope of the present invention.

[0027] In the following examples and comparative examples, the adsorption performance of the adsorbent is evaluated by the adsorption amount of the prepared adsorbent. The nitrogen adsorption amount test is carried out at 25° C. and 1 bar, using high-purity nitrogen.

[0028] Example 1

[0029] Prepare raw material 1 containing 5.7kg 4A raw powder and 0.7kg attapulgite (attapulgite content 10.9%), and perform water spray granulation in a ball-making device. When the particle size of the spherical material reaches 1.0mm, use raw material 2 containing 64.3kg 4A raw powder and 29.3kg attapulgite (attapulgite content 31.3%) to continue granulation until the particle size of the spherical material reaches the target particle size of 2.5mm, and stop granulation. The obtained material is dried, roasted at 750℃ for 6h, treated with 50% mass fraction NaOH solution at 92℃ for 240min, and then dried at 120℃ for 5h and roasted at 450℃ for 4h to obtain the target product.

[0030] Example 2

[0031] Prepare raw material 1 containing 9.1kg 13X original powder and 2kg bentonite (bentonite content 18.1%), and perform water spray granulation in a ball-making device. When the particle size of the spherical material reaches 1.2mm, use raw material 2 containing 65.9kg 13X original powder and 23kg bentonite (bentonite content 25.9%) to continue granulation until the particle size of the spherical material reaches the target particle size of 2.5mm, and stop granulation. The obtained material is dried, roasted at 700℃ for 4.5h, treated with 40% mass fraction NaOH solution at 85℃ for 200min, and then dried at 110℃ for 7h and roasted at 500℃ for 4.5h to obtain the target product.

[0032] Example 3

[0033] Prepare raw material 1 containing 18.1kg 4A raw powder and 3.5kg bentonite (bentonite content 16.2%), and perform water spray granulation in the ball making equipment. When the particle size of the spherical material reaches 1.5mm, use raw material 2 containing 56.9kg 4A raw powder and 21.5kg bentonite (bentonite content 27.4%) to continue granulation until the particle size of the spherical material reaches the target particle size of 2.5mm, and stop granulation. The obtained material is dried, roasted at 720℃ for 5h, treated with 45% mass fraction NaOH solution at 80℃ for 280min, and then dried at 115℃ for 4h and roasted at 400℃ for 3.5h to obtain the target product.

[0034] Example 4

[0035] Prepare raw material 1 (kaolin content 9.5%) containing 1.7kg 13X raw powder and 0.18kg kaolin, and perform water spray granulation in the ball making equipment. When the particle size of the spherical material reaches 0.8mm, use raw material 2 (kaolin content 13.3%) containing 25.7kg 13X raw powder and 3.9kg kaolin to continue granulation. When the particle size of the spherical material reaches 2mm, use raw material 3 (kaolin content 23.2%) containing 52.6kg 13X raw powder and 15.9kg kaolin to continue granulation until the particle size of the spherical material reaches the target particle size of 3mm, and stop granulation. The obtained material is dried, roasted at 650℃ for 6.5h, treated with 48% mass fraction NaOH solution at 90℃ for 220min, and then dried at 100℃ for 6.5h and roasted at 380℃ for 5h to obtain the target product.

[0036] Example 5

[0037] Prepare raw material 1 (kaolin content 15%) containing 0.68kg 4A raw powder and 0.12kg kaolin, and perform water spray granulation in a ball-making device. When the particle size of the spherical material reaches 0.6mm, use raw material 2 (kaolin content 22%) containing 9.75kg 4A raw powder and 2.75kg kaolin to continue granulation. When the particle size of the spherical material reaches 1.5mm, use raw material 3 (kaolin content 31.3%) containing 59.6kg 4A raw powder and 27.1kg kaolin to continue granulation until the particle size of the spherical material reaches the target particle size of 3mm, and stop granulation. The obtained material is dried, roasted at 700℃ for 5.5h, treated with 40% mass fraction NaOH solution at 95℃ for 180min, and then dried at 130℃ for 8h and roasted at 420℃ for 5.5h to obtain the target product.

[0038] Example 6

[0039] Raw material 1 containing 2.46kg 13X raw powder and 0.24kg attapulgite (attapulgite content 8.9%) was prepared, and water spray granulation was carried out in a ball-making equipment. When the particle size of the spherical material reached 0.9mm, raw material 2 containing 18.3kg 13X raw powder and 3.3kg attapulgite (attapulgite content 15.4%) was used to continue granulation. When the particle size of the spherical material reached 1.8mm, raw material 3 containing 59.3kg 13X raw powder and 16.4kg attapulgite (attapulgite content 21.7%) was used to continue granulation, until the particle size of the spherical material reached the target particle size of 3mm, and the granulation was stopped. The obtained material was dried, calcined at 730°C for 7h, treated with 52% by mass NaOH solution at 92°C for 260min, dried at 100°C for 5.5h, and calcined at 470°C for 4h to obtain the target product.

[0040] Comparative Example 1

[0041] Prepare a raw material containing 65kg 4A raw powder and 35kg attapulgite (attapulgite content 35%), and perform water spray granulation in a ball-making device until the particle size of the spherical material reaches the target particle size of 2.5mm, and then stop granulation. The obtained material is roasted at 750℃ for 6h, treated with 50% NaOH solution at 92℃ for 240min, and then dried at 120℃ for 5h and roasted at 450℃ for 4h to obtain the target product.

[0042] Comparative Example 2

[0043] Prepare a raw material containing 70kg 13X raw powder and 30kg bentonite (bentonite content 30%), and perform water spray granulation in a pelletizing device until the particle size of the spherical material reaches the target particle size of 2.5mm, then stop granulation. The obtained material is roasted at 700℃ for 4.5h, treated with 40% mass fraction NaOH solution at 85℃ for 200min, and then dried at 110℃ for 7h and roasted at 500℃ for 4.5h to obtain the target product.

[0044] Comparative Example 3

[0045] Prepare a raw material containing 70kg 4A powder and 30kg bentonite (bentonite content 30%), and perform water spray granulation in a pelletizing device until the particle size of the spherical material reaches the target particle size of 2.5mm, then stop granulation. The obtained material is roasted at 720℃ for 5h, treated with 45% NaOH solution at 80℃ for 280min, dried at 115℃ for 4h, and roasted at 400℃ for 3.5h to obtain the target product.

[0046] Comparative Example 4

[0047] Prepare a raw material containing 75kg 13X raw powder and 25kg kaolin (kaolin content 25%), and perform water spray granulation in a ball-making device until the particle size of the spherical material reaches the target particle size of 3mm, then stop granulation. The obtained material is roasted at 650℃ for 6.5h, treated with 48% NaOH solution at 90℃ for 220min, dried at 100℃ for 6.5h, and roasted at 380℃ for 5h to obtain the target product.

[0048] Comparative Example 5

[0049] Prepare a raw material containing 65kg 4A raw powder and 35kg kaolin (kaolin content 35%), and perform water spray granulation in a ball-making device until the particle size of the spherical material reaches the target particle size of 3mm, then stop granulation. The obtained material is roasted at 700℃ for 5.5h, treated with 40% NaOH solution at 95℃ for 180min, dried at 130℃ for 8h, and roasted at 420℃ for 5.5h to obtain the target product.

[0050] Comparative Example 6

[0051] Prepare a raw material containing 75kg 13X raw powder and 25kg attapulgite (attapulgite content 25%), and perform water spray granulation in a ball-making device until the particle size of the spherical material reaches the target particle size of 3mm, and then stop granulation. The obtained material is roasted at 730℃ for 7h, treated with a 52% mass fraction NaOH solution at 92℃ for 260min, and then dried at 100℃ for 5.5h and roasted at 470℃ for 4h to obtain the target product.

[0052] Table 1

[0053]

Claims

1. A method for preparing a multilayer core-shell structure adsorbent, comprising the following steps: (1) preparing N kinds of mixtures composed of adsorbent raw powder and binder with different binder mass percentages, respectively, in the order of binder mass percentage from low to high, namely mixture 1, mixture 2, ..., mixture N-1 and mixture N, wherein the binder mass percentages of two adjacent mixtures differ by 5-50 percentage points; (2) Adding a powder mixture to a ball rolling machine for water sprinkling molding, and adding raw materials with different binder mass percentages at different stages of molding; specifically, the method includes: first, adding mixture 1 to the ball rolling machine for water sprinkling molding; when the diameter of the spherical particles reaches d1, replacing the powder with mixture 2, and continuing the water sprinkling molding; when the diameter of the spherical particles reaches d2, replacing the powder with mixture 3, ..., when the diameter of the spherical particles reaches dN-1, switching the powder to mixture N, and continuing the water sprinkling molding until the diameter of the spherical particles reaches the designed particle size d, and the ball rolling is terminated; (3) post-treating the spherical particle molded body obtained in step (2), drying and calcining to obtain the target adsorbent; Wherein, N is a natural number, and its value can be any value between 2 and 5; The adsorbent raw powder is selected from at least one of A-type molecular sieve, X-type molecular sieve, Y-type molecular sieve, ZSM-5 type molecular sieve, and SAPO type molecular sieve; the binder is selected from at least one of kaolin, attapulgite, and bentonite.

2. The preparation method according to claim 1, characterized in that: N is 2 or 3.

3. The preparation method according to claim 1, characterized in that: In the N kinds of mixed materials, the mass percentage of the binder is 5%-70%.

4. The preparation method according to claim 3, characterized in that: In the N kinds of mixed materials, the mass percentage of the binder is 7% to 60%.

5. The preparation method according to claim 1, characterized in that In step (2), d1 is 0.05-0.7 times the designed particle size d, and the difference between the diameters of two adjacent particles is 0.1-0.5 d.

6. The preparation method according to claim 1 or 5, characterized in that: When N is 2, d1 is 0.05-0.7 d.

7. The preparation method according to claim 6, characterized in that: The mass percentage of the binder in mixture 1 is 5%-30%, and the mass percentage of the binder in mixture 2 is 15%-70%.

8. The preparation method according to claim 1, characterized in that When N is 3, d1 is 0.05-0.7 d and d2 is 0.5-0.9 d.

9. The preparation method according to claim 8, characterized in that: The mass percentage of the binder in Mix 1 is 5%-20%, the mass percentage of the binder in Mix 2 is 10%-60%, and the mass percentage of the binder in Mix 3 is 15%-70%.

10. The preparation method according to claim 1, characterized in that: The designed particle size d ranges from 0.1 to 10 mm.

11. The preparation method according to claim 10, characterized in that: The designed particle size d ranges from 0.5 to 5 mm.

12. The preparation method according to claim 1, characterized in that: The post-treatment in step (3) includes at least one of calcination, alkali treatment and calcium ion exchange.

13. The preparation method according to claim 12, characterized in that: The post-treatment calcination temperature in step (3) is 300-850°C, and the calcination time is 1-10h.

14. The preparation method according to claim 13, characterized in that: The post-treatment calcination temperature in step (3) is 350-800°C, and the calcination time is 2-8h.

15. The preparation method according to claim 12, characterized in that: The alkali treatment described in step (3) is carried out using an alkaline aqueous solution, the alkaline substance is selected from at least one of NaOH, KOH, Ca(OH)2, Na2CO3, NaHCO3, K2CO3, and KHCO3, and the mass content of the alkaline substance in the alkaline aqueous solution is 5% to 60%.

16. The preparation method according to claim 15, characterized in that: The mass content of the alkaline substance in the aqueous solution in step (3) is 10% to 55%.

17. The preparation method according to claim 15, characterized in that: After adding the alkaline substance in step (3), the aqueous solution is heated to 45-100° C. and the insulation time is 20-400 min.

18. The preparation method according to claim 17, characterized in that: After adding the alkaline substance in step (3), the aqueous solution is heated to 50-97° C. and the heat preservation time is 30-300 min.

19. The preparation method according to claim 1, characterized in that: The drying conditions in step (3) are: drying temperature of 45-150°C, and drying time of 0.1-15h; the roasting conditions are: roasting temperature of 250-700°C, and roasting time of 0.5-10h.

20. The preparation method according to claim 1, characterized in that: The drying conditions in step (3) are: drying temperature of 50-140°C, and drying time of 0.5-12h; the roasting conditions are: roasting temperature of 300-650°C, and roasting time of 1-8h.

21. A multi-layer core-shell structure adsorbent prepared by the method according to any one of claims 1 to 20.

Citation Information

Patent Citations

  • A binder-free spherical 5A molecular sieve adsorbent and its preparation method

    CN109692658B

  • Antiwear spherical NaY molecular sieve and its synthesizing process

    CN1393399A

  • Core-shell type molecular sieve microsphere as well as preparation method and application thereof

    CN104492405A

  • 5A molecular sieve adsorbent as well as preparation method and application thereof

    CN109772261A